The impact of some financial variables on the financial sustainability of Ira (Eurasian Journal of History, Geography and Economics, 2023)
All countries, including Iraq, seek to achieve financial sustainability by ensuring the ability to continue in the policies of public expenditures and public revenues in the long term without reducing financial solvency or exposure to risks of bankruptcy or failure to fulfill future financial obligations, and on this basis the research aims to measure and analyze the impact of some variables Finance (oil revenues, tax revenues, other revenues and public debt) in the financial sustainability of Iraq through the use of a modern standard model to assess financial sustainability in the Iraqi economy during the period 2004-2022, and the research found that there is a short-term relationship between all indicators of financial sustainability and the indicator Net Budget/GDP at the 5% significant level. The research also found that there is a long-term relationship between the independent variable X1 and the dependent variable Y, and that the other independent variables X2, X3, X4 did not have a direct effect on Y represented by (the ratio of net budget / GDP), and the research recommended the need to work on Diversifying sources of income to increase non-oil revenues by creating an investment environment that suits the nature of economic resources in a way that contributes to raising the level of public revenues and reduces the impact of fluctuations in oil prices, as well as reviewing financial and monetary policies with the necessity of coordination between them in a way that leads to achieving financial sustainability .